(3GdfXQjGJ GdEbJUGOjI GdcdjI HEbJUGO eZdb (B:s (3gd GdSjGSGJ GdfbOjI hGdeGdjI ddHdOGf aYGdI HeG jcaj? (B/s - (3Hf YGHO, eNJGQs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3JWhQGJ GdacQ GdfXQj GdJbdjOj GdfbOj hGdeGdj GdYehej heMOO bjeI GdfbhO HGdeOjjf GdbUjQ hGdWhjd HGdJMdjd GdcdGSjcj, fehPL bGfhf GdYQV hGdWdH eY JWhQ GdcJdI GdfbOjI hGdCSYGQ ddGfJGL aj GdhdGjGJ GdeJMOI NdGd aJQI (B1990- 1963(3, cPdc JhGRf GdGbJUGO Gdcdj dOi GdacQ GdJbdjOj eY JMOjO JhGRf GdbWGYjf GdMbjbj hGdfbOj HGdGVGaI Gdi JhGRf Shb GdYed eMOO dMLe GdGfJGL Gdcdj HGdfehPL GdJbdjOj(B. (3eY GfOaGYI cjfR hJWhjQ fehPLg (BIS-LM (3hCNjQG GdeaGVdI Hjf GdCgOGa Ydi GdeOi GdbUjQ eY aYGdjI GdSjGSJjf GdfbOjI hGdeGdjI dOi efMfi (Bphilips (3GdCSGSjI(B.s
(3eQGLY U(B.413- 420s
Keywords: (3GdGbJUGO Gdcdjs; (3GdSjGSI GdeGdjIs; (3GdfXGe GdfbOjs